Kepastian Hukum Electric Vehicle dalam Menunjang Pendistribusian Barang sebagai Implementasi Green Logistics di Indonesia - Nuhi, Muhammad Hanan; As'ad Al Muqsid, Sulthan; Tiara Salsabila, Fara; Salsabill (Forschungsforum Law Journal, 2025)
Based on research by the Institute for Management Development (IMD) in 2024, Indonesia's economy is growing every year, where in 2024, Indonesia was in 27th position out of 67 countries, in 2023 Indonesia was in 34th position. Economic growth, especially in trade, has created an increase in demand for logistics activities. However, logistics activities also have an impact on the environment. Based on the 2022 ADB (Asian Development Bank) Report, the transportation sector contributes around 15–20% of CO₂ emissions in Southeast Asia, with logistics transportation as the main contributor. In this case, the solution that can be applied is the use of electric vehicles (Electric Vehicles, hereinafter abbreviated as EV). The government itself has encouraged the adoption of EVs through regulatory policies, but these regulations have not provided optimal legal certainty. This study uses a normative legal method with a statute approach and a comparative approach. With this research method, the study not only highlights the legal aspects but also the practical obstacles in the implementation of EVs, so that it can provide a more comprehensive picture of the effectiveness of regulations and the solutions needed. The results of the study show that the application of EV in green logistics is in line with Indonesia's commitment to sustainable development and the principles of a green economy which are also in line with the Theory of Development Law put forward by Prof. Dr. Mochtar Kusumaatmadja. EVs are expected to support the realization of a more environmentally friendly distribution of goods, especially considering Indonesia's goal of achieving Net Zero Emission. However, based on existing regulations, derivative regulations are still needed that can provide legal certainty for EVs in supporting the distribution of goods, especially as legal certainty for the implementation of green logistics in Indonesia.